Synthesis of Mesoporous SiO2@TiO2 Core/Shell Nanospheres with Enhanced Photocatalytic Properties. (8th February 2013) - Hu, Jin‐Lin; Qian, Hai‐Sheng; Li, Jia‐Jia; Hu, Yong; Li, Zheng‐Quan; Yu, Shu‐Hong
<x xml:space="preserve">Abstract</x> Mesoporous SiO2@TiO2 core/shell nanospheres with a specific surface area of 567–673 m2 g−1 and an average pore size of 1.5–2.8 nm are successfully prepared using a facile method combining sol‐gel and thermal treatment processes. The nanospheres exhibit excellent adsorption capability and photodegradation toward rhodamine B (RhB) in pollutant solution. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>